Inhibitory mechanism of morin on α-glucosidase and its anti-glycation properties. Issue 9 (23rd August 2016) - Zeng, Li; Zhang, Guowen; Liao, Yijing; Gong, Deming
Abstract : Morin can inhibit the activity of α-glucosidase and attenuate the generation of AGEs both related to diabetes mellitus. Abstract : It is important to investigate the inhibition of α-glucosidase due to its correlation with type 2 diabetes. Morin was found to exert significant inhibition activity on α-glucosidase in a reversible mixed-type manner with an IC50 value of (4.48 ± 0.04) μM. Analyses of fluorescence and circular dichroism spectra indicated that the formation of the morin-α-glucosidase complex was driven mainly by hydrophobic forces and hydrogen bonding, and caused the conformational changes of α-glucosidase. The phase diagrams of fluorescence showed that the conformational change process was monophasic without intermediates. Molecular docking indicated that morin mainly interacted with amino acid residues located close to the active site of α-glucosidase, which may move to cover the active pocket to reduce the binding of the substrate and then inhibit the catalytic activity. Morin was also found to exhibit inhibition in the generation of advanced glycation end products which was related to the long term complications of diabetes.